Implantation sites after embryo transfer into the central area of the uterine cavity - Cavagna, M.; Contart, P.; Petersen, C. G. [UNESP]; Mauri, A. L. [UNESP]; Martins, A. M C [UNESP]; Baruffi, R. L R; Oliveira, J. B A; Franco, J. G. [UNESP] (Elsevier, 2006)
A total of 63 pregnancies (47 singleton, 15 twin, 1 triplet) from intracytoplasmic sperm injection cycles were analysed. In all embryo transfers, the catheter was introduced into the endometrial cavity guided by abdominal ultrasound, with the catheter tip placed at the middle point of the endometrial cavity. Gestational sacs (GS) were located 21-24 days after transfer (gestational age = 5 weeks) by two-dimensional and three-dimensional transvaginal ultrasound. The uterine cavity was divided into three parts: upper, middle and lower. Furthermore, the upper region was subdivided into right, middle and left areas, and the middle region was subdivided into right and left areas. The frequency of gestational sacs in each area was evaluated. In singleton pregnancies 66.0% (31/47) of the GS were detected in the upper region, 29.8% (14/47) in the middle region and 4.2% (2/47) in the lower region. In multiple pregnancies (twins and triplet) 45.5% (15/33) of the GS were detected in the upper region, 51.5% (17/33) in the middle region and 3.0% (1/33) in the lower region. In conclusion, the results demonstrate that when embryos are transferred to the central area of the uterine cavity there is an increase in implantation rate in the middle region compared with the rate expected in naturally conceived pregnancies (9-15%).
Keywords: Embryo transfer; Gestational sac; Implantation site; Ultrasound; adult; catheter; controlled study; echography; embryo transfer; embryonic structures; female; gestational age; human; intracytoplasmic sperm injection; major clinical study; multiple pregnancy; nidation; pregnancy; transvaginal echography; uterus cavity; Abortion, Spontaneous; Adult; Embryo Implantation; Embryo Transfer; Female; Humans; Pregnancy; Pregnancy, Multiple; Sperm Injections, Intracytoplasmic; Ultrasonography, Prenatal; Uterus